Leveraging EdTech in Curriculum Reform: An Evaluation Toward Sustainable Educational Outcomes - Husna, Fatimatul (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to evaluate the integration of educational technology in curriculum reform at pesantren-based vocational schools in responding to the challenges of the Industrial Revolution 4.0. The research employed a qualitative case study design. Data were collected through field observations, in-depth interviews, Focus Group Discussions, analysis of digital documents, and questionnaires administered to productive teachers and students of the Software Engineering and Computer and Network Engineering programs. The analysis process was carried out through data reduction, narrative presentation, and cross-verification among sources, using content, discourse, and interpretive analyses. The findings reveal that the use of the NOBOX.AI platform improved module completion rates by up to 73%, reduced assignment dropouts by 21%, and decreased paper usage. Industry collaboration through internships, teacher training, and teaching factory programs enhanced the relevance of students’ skills to real workplace demands. However, challenges such as limited digital infrastructure and teachers’ readiness remain significant obstacles. The implications of this study highlight the need to strengthen teacher capacity, expand equitable digital infrastructure, and ensure the sustainability of industry partnerships so that technology integration can truly foster an adaptive, relevant, and sustainable curriculum. These findings may serve as a valuable reference in formulating vocational education policies in pesantren-based contexts that are responsive to contemporary transformations.